Increasing incidence of normal pressure hydrocephalus in Germany: an analysis of the Federal Statistical Office Database from 2005 to 2022 - Santhosh G. Thavarajasingam; Ahmed Salih; Srikar R. Namireddy; Florian Ringel; Andreas Kramer (Scientific Reports)
Abstract Normal pressure hydrocephalus (NPH) is a reversible cause of gait disturbances and dementia in the elderly, posing diagnostic and therapeutic challenges. In Germany, the epidemiology and surgical management of NPH are not well understood. This study aimed to characterise epidemiological trends and evaluate surgical management strategies for NPH in Germany. A retrospective nationwide population-based study of NPH cases in Germany from 2005 to 2022 was conducted using data from the German Federal Statistical Office. Parameters assessed included incidence trends, demographic characteristics, and surgical interventions. A total of 118,526 NPH diagnoses were recorded, with 29,662 surgical interventions. The population-adjusted incidence of NPH increased by 48%, from 5.4 to 8.0 cases per 100,000 individuals (p < 0.001), peaking in 2018. The largest increases were seen in the “80–89” age group, followed by the “70–79” and “90+” age groups. Surgical interventions increased by 8.4% (p < 0.001), with ventriculoperitoneal shunt being the predominant procedure. The study highlights a 48% rise in NPH incidence in Germany from 2005 to 2022, particularly affecting the elderly. There was also an increase in surgical interventions, underscoring the need for prioritising NPH in national healthcare research agendas.